Pengaruh Perendaman Akar Bibit Bayam Merah (Alternanthera amoena Voss.) dalam Larutan Na2CuEDTA terhadap Pertumbuhan dan Kandungan Antosianin - Aini, Nabilah; Nurchayati, Yulita; Suedy, Sri Widodo Agung (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Red spinach is one of plants containing anthocyanin pigment which has various functions as food and beverage dye, and play a role in the field of health. Anthocyanin biosynthesis in plants is influenced by environmental factors, one of them are nutrients. One of the nutrients needed by plants and part of the anthocyanin biosynthesis pathway is copper (Cu). Cu can be added in the form of a fertilizer such as Na2CuEDTA. This research aims to study the effect of soaking the red spinach in Na2CuEDTA solution on growth and anthocyanin content, and knowing the optimal Na2CuEDTA concentration for growth and anthocyanin content of red spinach. This research conduct to Complete Random Design of single factor pattern with 5 treatments and 5 replications which are aquades, nutrient solution, nutrient solution+Na2CuEDTA 5 ppm, nutrient solution+Na2CuEDTA 10 ppm, nutrient solution+Na2CuEDTA 20 ppm. Sprouts red spinach that already has 4 leaves soaked in the treatment solution for 10 days, then the plants moved into a soil medium inside the pot for 20 days. The analyzing data which is used is ANOVA continuing with further testing of Duncan Multiple Range Test (DMRT) at the 95% significance level. The result of this research show that soaking of red spinach in Na2CuEDTA solution did not show any significant effect on growth. The growth of red spinach plant is more influenced by nutrient solution while the anthocyanin contents is influenced by nutrients in soil medium.Â Key words : Red Spinach, Copper, Anthocyanin, Na2CuEDTA